2018
DOI: 10.1007/s10973-018-7047-8
|View full text |Cite
|
Sign up to set email alerts
|

The influence of smartphones’ operation modes on the superficial temperature distribution in the human auricle region

Abstract: In this study, the infrared thermography was used to examine heating effects in human auricle region due to short-duration use of smartphones in normal and flight mode operation by 20 healthy volunteers (age 19-24 years, 9 females and 11 males). Statistically significant differences in both modes were observed between mean temperatures of the auricle regions before and immediately after the use of the smartphone. The increase in tissue temperature resulted from a combined effect of conductive heat transfer cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 51 publications
0
17
0
1
Order By: Relevance
“…Though, linking this with a mobile phone battery model a total overarching simulation for mobile phone thermal effects can be determined. These results will present a more comparable model with clinical test trials for mobile phone use, as in Bauer et al (2018).…”
Section: Estimation Of Sarmentioning
confidence: 92%
See 2 more Smart Citations
“…Though, linking this with a mobile phone battery model a total overarching simulation for mobile phone thermal effects can be determined. These results will present a more comparable model with clinical test trials for mobile phone use, as in Bauer et al (2018).…”
Section: Estimation Of Sarmentioning
confidence: 92%
“…We compared the simulated data with thermographic images taken by Bauer et al (2018) that examined heating effects of smartphones on the human auricle region. Fig.…”
Section: Complete Head Model With Simulation Of Mobile Phone Heatingmentioning
confidence: 99%
See 1 more Smart Citation
“…Al-Mously (2010) measured the temperature increase in two mobile phone chases, candy bar type Motorola L71 and clamshell type Motorola RAZR V3i, after 60 min call, and then, the two mobile phones were simulated, using 3D EM simulation software, in close proximity to head at cheek position to measure the temperature increase in pinna tissue due to thermal conduction. Bauer, et al (2018) investigated the influence of smartphones' operation modes on the superficial temperature distribution in the human pinna region. He observed that there are statistically significant differences between mean temperatures of the pinna before and immediately after the use of the smartphone, independent of whether RF communication was on (normal mode) or off (flight mode).…”
Section: Introductionmentioning
confidence: 99%
“…Infrared (IR) thermography, in contrast, does not require any direct contact with the patient and allows remote and non-contact assessment of the surface temperature distribution of the examined body [28,29]. The method is widely used for superficial temperature distribution' measurements in medicine, e.g., screening tests [30], prevention [31], diagnosis [32,33], treatment' assessment [34][35][36], physiotherapy [37,38] as well as personalized medicine [39,40].…”
Section: Introductionmentioning
confidence: 99%